2016
DOI: 10.5897/jphe2015.0795
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, risk perception and hepatitis B vaccination status of healthcare workers in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria

Abstract: Hepatitis B virus (HBV) infection threatens the health of populations across the globe. It is an important occupational risk for health care workers (HCWs); they are known to be at high risk of the infection following needle stick injuries and accidental exposure to infected blood and other body fluids. This study was conducted to assess the knowledge, risk perception and hepatitis B vaccination status of HCWs in Usmanu Danfodiyo University Teaching Hospital (UDUTH), Sokoto, Nigeria. A descriptive cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 19 publications
11
24
4
Order By: Relevance
“…In this study we found that only 56.37% of participants had got vaccinated against HBV. Which is higher than study results from japan (48.2%) [26] and Nigeria (40.3%) [21].. From those health care workers who had got vaccinated, only 5.17% had completed three doses of vaccine. This is much lower level of complete vaccination when compared with other studies.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study we found that only 56.37% of participants had got vaccinated against HBV. Which is higher than study results from japan (48.2%) [26] and Nigeria (40.3%) [21].. From those health care workers who had got vaccinated, only 5.17% had completed three doses of vaccine. This is much lower level of complete vaccination when compared with other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…This is much lower level of complete vaccination when compared with other studies. However, Nigeria, 56.0% of respondents that have been vaccinated against HBV infection had the recommended three doses of the vaccine [21] Conclusions…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have shown that HCPs are at higher risk of acquiring HBV than the general population 4,6,20,21. It has been estimated that approximately 6,200 HBV infections occur each year among HCPs in Sub-Saharan African 9,22. A good knowledge of HBV virus and modes of infection as well as adequate vaccination may reduce infection rate 2.…”
Section: Discussionmentioning
confidence: 99%
“…Health care professionals (HCPs) are at increased risk of acquiring hepatitis B infection due to occupational exposure 1,3,9. In one study, HCPs were shown to have up to a fourfold increased risk of acquiring HBV infection 10.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, testing the level of HCWs' hepatitis B awareness is of tremendous importance, considering the fact that knowledge is crucial factor for prevention-related behaviour modification. Keeping this public health problem in mind, over the past years increasing numbers of studies has been dealing with this particular issue 9,13,14,16,[18][19][20] . Therefore, the present study conducted in Serbian health care setting aimed at addressing this challenge.…”
Section: Discussionmentioning
confidence: 99%